Analisis Tindak Tutur Ilokusi pada Daftar Putar Maudy Ayunda’s Booklist dalam Kanal Youtube Maudy Ayunda - Khariztma Nuril Qolbi Barlanti; Feny Amanda Primasari; Lusi Murdiani; Firda Rubiyanti Desvika Sari; Cahyani Ismi Azizah; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Illocutionary speaking acts are frequently used in social interactions. The discovery is significant because illocutionary speech acts can influence others to take action. The purpose of this research is to classify the form, function, and kind of illocutionary speech actions in addition to providing information about illocutionary speech acts that are employed in daily life. In this study, a pragmatic theoretical approach and a qualitative descriptive methodological technique were both used. Five videos from the Maudy Ayunda's Booklist playlist on her YouTube channel serve as the data source. The process of reviewing the data involved using note-taking and listening strategies. As data analysis tools, distributional method and identify method are employed in the interim. The results were achieved by finding forms of illocutionary speech acts with a declarative form which contains information, an imperative form which contains a command, and an interrogative form which states a question. Based on the types of illocutionary speech acts, the assertive types of telling and stating, the directive types of ordering and suggesting, the commissive types of promising and offering, the expressive types of congratulations and thanks, and the declarative types of agreement and decide are found. Meanwhile, based on the function of illocutionary speech acts, the fun function of praising and thanking was found, as well as the function of working together to teach and express.